A Comparison of Contemporary Chinese and America Youth Cinemas’ Portraits of Young People in School - Song, Wang Chang; Hashim, Rohani (Jurnal Pengajian Media Malaysia, 2014)
This study discusses the differences between Chinese youth film and American teen film through the perspective on cultural foundation. The authors argue that Confucianism is an alternative that greatly affects the depiction of young characters and the causal relationship of morality and fate of the characters in films. The objective of such a comparison is not to advocate for either Chinese or American youth cinema in portraying young people, but to promote a better understanding of the strengths and impacts of youth cinema and youth genre. In addition, this study examines cinematic depictions of young characters portrayed in Chinese youth films and American teen films. It is argued that Chinese youth films and American youth films differ in depictions of school settings and even their purposes.